Phospholipase Cδ regulates germination of Dictyostelium spores - Van Dijken, Peter (BioMed Central, 2001)
BACKGROUND: Many eukaryotes, including plants and fungi make spores that resist severe environmental stress. The micro-organism Dictyostelium contains a single phospholipase C gene (PLC); deletion of the gene has no effect on growth, cell movement and differentiation. In this report we show that PLC is essential to sense the environment of food-activated spores. RESULTS: Plc-null spores germinate at alkaline pH, reduced temperature or increased osmolarity, conditions at which the emerging amoebae can not grow. In contrast, food-activated wild-type spores return to dormancy till conditions in the environment allow growth. The analysis of inositol 1,4,5-trisphosphate (IP(3)) levels and the effect of added IP(3) uncover an unexpected mechanism how PLC regulates spore germination: i) deletion of PLC induces the enhanced activity of an IP(5) phosphatase leading to high IP(3) levels in plc-null cells; ii) in wild-type spores unfavourable conditions inhibit PLC leading to a reduction of IP(3) levels; addition of exogenous IP(3) to wild-type spores induces germination at unfavourable conditions; iii) in plc-null spores IP(3) levels remain high, also at unfavourable environmental conditions. CONCLUSIONS: The results imply that environmental conditions regulate PLC activity and that IP(3) induces spore germination; the uncontrolled germination of plc-null spores is not due to a lack of PLC activity but to the constitutive activation of an alternative IP(3)-forming pathway.